Translation and Psychometric Analysis of the Brief Symptom Inventory in Adolescents with Substance Use Disorder - Yanuarti, Tuty; Daud, Mohd Nazri Bin Mohd; Mohamed, Noor Hassline Binti; Atil, Azman Bin (Jurnal Kesehatan Masyarakat, 2025)
The Brief Symptom Inventory-18 (BSI-18) is an 18-item self-report checklist designed to screen for psychological symptoms in medical patients. This study aimed to assess the psychometric properties of BSI among a diverse group of Indonesian adolescents. This study involved 80 15 to 18-year-old adolescents from a drug rehabilitation center in West Java, Indonesia. The instrument was translated into Bahasa Indonesia, and its content validity index was calculated using Aiken’s V formula. The CVI ranged from 0.73 to 1.00 for BSI. The factor loadings of each of the three scales in the BSI ranged from 0.43 and 0.88. The model was acceptable and appropriate when confirmatory factor analyses of the BSI were conducted. The Cronbach alpha coefficient of the BSI was 0.925. The findings of this study give evidence that the BSI is a viable and beneficial screening tool for detecting substance use problems among Indonesian adolescents.